THE EFFECTIVENESS OF THE SIDOARJO MATERNAL NEONATAL EMERGENCY SMS APPLICATION GATEWAY (SIMANEIS) IN IMPROVING HEALTH SERVICES - Hertati, Diana (DIA: Jurnal Administrasi Publik, 2023)
With the innovation of health services based on Sidoarjo Maternal Neonatal Emergency Sms Gateway (SIMANEIS), pregnant women, patients can go to the midwife, clinic and or PUSKESMAS first to get an initial diagnosis, which is then referred from the clinic or health center to the hospital through SIMANEIS so that when in the hospital can be handled immediately. However, the reality in the field is that the implementation of Si Maneis' innovation is still not effective due to the unprofessional attitude of the officers, the internet connection network that often errors. Based on these problems, the purpose of this study was to determine and describe the effectiveness of the Sidoarjo Maternal Neonatal Emergency SMS Gateway (SIMANEIS) Application in Improving Health Services. The research method used is descriptive research with a qualitative approach. Data was collected by means of observation, interviews, and documentation. The research location is the RSUD Sidoarjo. Methods of data collection is done by using interviews, focused groups and discussion. Data analysis was carried out using qualitative analysis by Miles and Huberman (2014) consisting of four components, namely: data collection, condensation data, display data and conclusion and verifying drawings. The result of the research is that the resources and infrastructure have been effective. The number and quality of services produced in the implementation of maternal and child referral administrative services based on Sidoarjo Maternal Neonatal Emergency SMS Gateway (SIMANEIS) at the Sidoarjo Regional General Hospital is running effectively. Meanwhile, the suitability of the service results has been effective, as evidenced by the officers giving real-time action in less than 5 minutes when a patient comes without lingering in accordance with the time standard that has been set. The service procedure that must be passed is quite easy and fast to be carried out according to the SOP.